2019
DOI: 10.3389/fcvm.2019.00168
|View full text |Cite
|
Sign up to set email alerts
|

How to Avoid Coronary Occlusion During TAVR Valve-in-Valve Procedures

Abstract: Transcatheter aortic valve-in-valve replacement has been recently reported as a less-invasive alternative to re-do surgery in patients with bioprosthetic valve failure. Although procedural success is achieved in the great majority of patients, this therapy is associated with several potential complications, and coronary occlusion is one of the most feared. This is a rare event, but it is associated with an extremely poor prognosis. In this review, the mechanisms, the identification of patients at high risk, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Coronary artery occlusion (CAO) has been reported as a rare but potentially lethal complication following SAVR, with a prevalence of 1%–5% of patients following SAVR 1–3 . This complication has also been reported after transcatheter aortic valve replacement and is usually associated with high mortality risk 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronary artery occlusion (CAO) has been reported as a rare but potentially lethal complication following SAVR, with a prevalence of 1%–5% of patients following SAVR 1–3 . This complication has also been reported after transcatheter aortic valve replacement and is usually associated with high mortality risk 4 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] This complication has also been reported after transcatheter aortic valve replacement and is usually associated with high mortality risk. 4 Clinical syndromes typically manifest within the first 6 months of the procedure and can range from stable angina to acute coronary syndrome, ventricular arrhythmias, heart failure, and even sudden cardiac death. This is the first case report to our knowledge of wire externalization and conversion to antegrade technique via a coronary ostium which was compressed from the AVR with a successful result.…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that new-generation valves are related to lower CO incidence in comparison to oldgeneration devices. New-generation valves, such as Lotus, Portico, and Evolut-R, could be easily retrieved during the procedure, 17) a function that may mitigate or recovery the CO if it happens. It is noteworthy that some new devices like Lotus were retrievable even after full implantation, while others like Portico could be retrieved only before it.…”
Section: Discussionmentioning
confidence: 99%
“…THV devices that could be immediately retrieved after partial device implantation may be the strategy of choice (e.g., Lotus, Portico, Evolut-R, etc.) to prevent such complications [107].…”
Section: Valve-in-valvementioning
confidence: 99%